Isolation and cloning of cytokinin oxidase 5 gene from Arabidopsis - Repalli, Sai Krishna; Baruah, Ananta M; Rai, Rhitu; Dash, Prasanta K. (Annals of Agricultural Research, 2016)
Phytohormones play intricate physiological and biochemical roles to control growth and development of plants. Amongst several phytohormones cytokinins (CKs) play an important role as they govern yield in crops. While controlling cardinal growth of plants, CKs govern a complex trait i.e. shoot apical meristem formation and there by yield in crops. Mutation studies on cytokinin oxidase (ckx) genes had revealed that decreased activity of cytokinin oxidase results in increased bioavailability of cytokinin and thereby increasing seed yield. In this study, we isolated ckx5 gene from Arabidopsis and cloned into an E coli vector so as to make it ready for mobilization into binary vector for future plant transformation experiments. Sequence of steps followed to clone the gene from Arabidopsis and confirm its presence were ncomphishel by (i) PCR based amplification with gene specific primers, (ii) restriction digestion followed by (iii) authentication of ckx gene by Sanger’s DNA-sequencing are discussed.